Synthesis of surfactant free stable nanofluids based on barium hexaferrite by pulsed laser ablation in liquid. Issue 34 (24th May 2018) - V. N., Archana; Johny, Jacob; Garza-Navarro, Marco A.; Shaji, S.; Thomas, Senoy; M. R., Anantharaman
Abstract : Barium hexaferrite nanofluids based on five different solvents are prepared using pulsed laser ablation in liquid, the different solvents resulting in different particle diameters. This study paves the way for the synthesis of stable magnetic nanofluids of permanent magnets. Abstract : Barium hexaferrite nanofluids based on five different solvents have been prepared by employing Pulsed Laser Ablation in Liquid (PLAL) at two different wavelengths of 532 nm and 1064 nm. They were then characterized using Transmission Electron Microscopy (TEM), Scanning Electron Microscopy (SEM), X-ray Photoelectron Spectroscopy (XPS), UV-Vis spectroscopy, and Vibrating Sample Magnetometry (VSM). The chemical states of the ablated nanoparticles were identified from XPS analysis and found to be matching with that of the target. The crystallinity of the nanoparticles were confirmed from high resolution TEM (HRTEM) images and SAED patterns. It is found that different liquid environments lead to the formation of barium ferrite nanoparticles with different particle diameters. The plausible mechanism involved in this process is discussed. This study can pave way for the synthesis of stable magnetic nanofluids of permanent magnets. Further, this technique could be utilized for tailoring the morphology of nanoparticles with a judicious choice of the solvents and other ablation parameters.